Gender Differences in Risk Factors Associated With Pulmonary Artery Systolic Pressure, Heart Failure, and Mortality in Blacks: Jackson Heart Study. Issue 1 (7th January 2020) - Lakshmanan, Suvasini; Jankowich, Matthew; Wu, Wen‐Chih; Blackshear, Chad; Abbasi, Siddique; Choudhary, Gaurav
Abstract : Background: Pulmonary hypertension is prevalent in black individuals, especially women. Elevated pulmonary artery systolic pressure (PASP) is associated with significant morbidity and mortality. Methods and Results: We developed linear and proportional hazards models to examine potential gender‐related differences in risk factors for elevated PASP (estimated by transthoracic echocardiography) and PASP‐associated clinical outcomes (incident heart failure admissions and mortality) in JHS (Jackson Heart Study) participants. JHS is a prospective observational cohort study of heart disease in blacks from the Jackson, Mississippi, metropolitan area. The study cohort included participants with measurable transtricuspid gradients (n=3286) at the time of first/baseline examination, 2000–2004. The median age (interquartile range) of patients at baseline was 57.8 years (18.6 years) with 67.5% being women. The median PASP at baseline was higher in women (men: 26 mm Hg [interquartile range 8], women: 27 mm Hg [interquartile range 9]. In multivariate linear regression analyses with PASP, significant gender interactions were noted for age, chronic lung disease, pulse pressure, and obstructive spirometry. In exploratory analyses stratified by gender, body mass index, and obstructive and restrictive spirometry patterns were associated with PASP in women, and chronic lung disease was associated with PASP in men. Age and pulse pressure had stronger associations with PASP in women compared with men. There was a significant interaction between gender and PASP for heart failure admissions but not mortality. Conclusions: Specific cardiopulmonary risk factors are associated with elevated PASP in women and men. Women with elevated PASP have a higher risk of incident heart failure admissions. Future research is needed to understand associated gender‐specific mechanisms that can help identify targeted prevention and management strategies for patients with elevated PASP.